1996
DOI: 10.1038/bjc.1996.62
|View full text |Cite
|
Sign up to set email alerts
|

LOH at 3p correlates with a poor survival in oral squamous cell carcinoma

Abstract: Summary We analysed chromosome 3p for loss of heterozygosity (LOH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
1
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 10 publications
0
46
1
1
Order By: Relevance
“…The existence of a putative tumor suppressor gene masked by allelic deletions is suggested by the correspondence of LOH with clinicopathological factors. LOH on 3p was reported to correlate with poor survival in lung and oral cancer (Mitsudomi et al 1996;Partridge et al 1996). These findings suggest a tumor suppressor gene on 3p involved in the development of several types of tumor.…”
Section: Introductionmentioning
confidence: 52%
“…The existence of a putative tumor suppressor gene masked by allelic deletions is suggested by the correspondence of LOH with clinicopathological factors. LOH on 3p was reported to correlate with poor survival in lung and oral cancer (Mitsudomi et al 1996;Partridge et al 1996). These findings suggest a tumor suppressor gene on 3p involved in the development of several types of tumor.…”
Section: Introductionmentioning
confidence: 52%
“…54 Overall, studies in HNSCC have shown that deletions at chromosome arms 3p, 4p, 8p and 9p represent early genetic changes and that loss at 18q, 17p and 11qter is associated with neoplastic progression. 33,34,36,45,48,55 Dysplastic regions in the head and neck region that show more LOH seem to be more at risk for neoplastic evolution. 17,18,19,33 There are several reports that LOH is associated with more advanced stage and more aggressive HNSCC tumors, 13,34,36,37,56 and specifically with nodal involvement.…”
Section: Lohmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) studies using microsatellite markers on head-and-neck malignancies have demonstrated extensive areas of loss. [1][2][3][4][5] Moreover, premalignant lesions studied in the initial description of a genetic progression model revealed the timing of genetic alterations such as LOH as premalignant lesions advance toward malignancy. 6 These specific genetic events can be detected in the saliva and serum of patients with head and neck malignancy, 7,8 opening the door to new strategies for early cancer detection and tumor surveillance.…”
mentioning
confidence: 99%